Pelaksanaan Nilai-Nilai Karakter Peserta Didik di Sekolah Dasar (Studi Kasus di SDN 14 KTK Kota Solok) - Ilham Febra; Nurhayati; Dina Dahliana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The weak implementation of character values ​​in students is a problem that requires attention in the implementation of basic education. This study aims to describe the implementation of character education in fifth-grade students at SDN 14 KTK, Solok City. The study used a qualitative approach with a case study method. Research informants consisted of the principal, teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman data analysis techniques which include data reduction, data presentation, and drawing conclusions. The results of the study indicate that character education is implemented through habituation activities, teacher role models, integration in the learning process, and a consistent school culture. The character values ​​developed include religiousness, discipline, honesty, responsibility, tolerance, social care, environmental care, and love of the homeland. The successful implementation of character education is supported by the involvement of all school members in creating a conducive environment for the formation of positive student behavior. Thus, character education at SDN 14 KTK, Solok City is not only oriented towards academic achievement, but also on the formation of student character in everyday life.